2016
DOI: 10.1371/journal.pone.0168255
|View full text |Cite
|
Sign up to set email alerts
|

GSK-3β/NFAT Signaling Is Involved in Testosterone-Induced Cardiac Myocyte Hypertrophy

Abstract: Testosterone induces cardiac hypertrophy through a mechanism that involves a concerted crosstalk between cytosolic and nuclear signaling pathways. Nuclear factor of activated T-cells (NFAT) is associated with the promotion of cardiac hypertrophy, glycogen synthase kinase-3β (GSK-3β) is considered to function as a negative regulator, mainly by modulating NFAT activity. However, the role played by calcineurin-NFAT and GSK-3β signaling in testosterone-induced cardiac hypertrophy has remained unknown. Here, we det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 61 publications
0
28
0
Order By: Relevance
“…Accordingly, NFAT-controlled gene transcription was found to involve additional transcription factors, including MEF2 ( Cortes et al, 2012 ). Recently, we determined that testosterone stimulates cardiac myocyte hypertrophy through NFAT activation and GSK-3β inhibition, which supports a cooperative mechanism involving cytoplasmic and nuclear signaling ( Duran et al, 2016 ).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Accordingly, NFAT-controlled gene transcription was found to involve additional transcription factors, including MEF2 ( Cortes et al, 2012 ). Recently, we determined that testosterone stimulates cardiac myocyte hypertrophy through NFAT activation and GSK-3β inhibition, which supports a cooperative mechanism involving cytoplasmic and nuclear signaling ( Duran et al, 2016 ).…”
Section: Discussionmentioning
confidence: 64%
“…Cardiac myocytes were cultured for 24 h and then incubated with [ 3 H]-leucine (2.5 μCi⋅mL -1 ) for an additional 48 h in the presence or absence of testosterone ( Duran et al, 2016 ). Next, the cells were washed four times with ice-cold PBS and treated with 10% trichloroacetic acid at 4°C for 60 min.…”
Section: Methodsmentioning
confidence: 99%
“…These transcription factors are dephosphorylated through calcineurin, a calcium-dependent phosphate that facilitates the nuclear translocation of NFAT [51]. In this regard, it is pertinent to mention a study that showed the increase in NFAT activity by testosterone and modulation of its transcriptional activity [52].…”
Section: Discussionmentioning
confidence: 99%
“…As an important regulator of myogenesis in mammal, GSK3β inhibition promotes myocyte differentiation manifested in the enhancement of myogenic regulatory factors such as myocyte enhancer factor 2 (MEF2) and MyoG (Dionyssiou et al, ), targeting insulin‐mediated myogenesis and activation of NFAT (Duran et al, ; Jl, Schols, Willems, Kelders, & Langen, ; Litwiniuk et al, ). Treatment of IGF‐1 or GSK3β inhibitor in differentiated C2C12 cells accelerates myogenesis shown in increased myotube formation, muscle creatine kinase (MCK) activity, and transactivation of troponin I (TnI) promoter, as well as increases the expression of MyoD, Myf5, myogenin, TnI‐slow, TnI‐fast, MCK, and myoglobin (Jl et al, ).…”
Section: Discussionmentioning
confidence: 99%